Generation Z Perception of Counterfeit Product Attribute and The Influence Toward Purchase Intention - Distiani Fitria Kusuma (Airlangga Journal of Innovation Management, 2021)
This research was conducted on 133 z generations of Indonesia. This study uses the Stimulus-Organism-Respondent model to explain counterfeit products' purchase intention in Generation z in Indonesia. This study uses SEM to analyze research results. This study's results indicate that the stimulus of past experience, product knowledge, product appearance, novelty-seeking, status consumption, and information susceptibility can affect the utilitarian and hedonic attitude of generation z towards imitation products. The utilitarian and hedonic attitudes of generation Z affect the counterfeit product purchase intention. These results can understand what stimuli can affect generation Z's attitude towards counterfeit products and how this affects the counterfeit product purchase intention.